Kuiyangling Enema Alleviates Ulcerative Colitis Mice by Reducing Levels of Intestinal NETs and Promoting HuR/VDR Signaling - Zhang D; Zhu Z; He Z; Duan S; Yi Q; Qiu M; Dai X; Su G; Li K; Xu L; Liu D; Wu Y; et al. (Journal of Inflammation Research)
Dong Zhang,1,2 Zeming Zhu,3 Zhangyou He,4 Siwei Duan,3 Qincheng Yi,4 Min Qiu,3 Xingzhen Dai,3 Guang Su,4 Kexin Li,1,2 Lin Xu,1,2 Donghou Liu,1,2 Yabin Wu,1,2 Yong Gao,3 Ruliu Li,3 Shaoju Guo1,2 1Gastroenterology Department, The Fourth Clinical Medical College of Guangzhou University of Chinese Medicine, Shenzhen, Guangdong Province, 518000, People’s Republic of China; 2Gastroenterology Department, Shenzhen Hospital of Traditional Chinese Medicine, Shenzhen, Guangdong Province, 518000, People’s Republic of China; 3Science and Technology Innovation Center, Guangzhou University of Chinese Medicine, Guangzhou, Guangdong Province, 510000, People’s Republic of China; 4Guangzhou University of Chinese Medicine, Guangzhou, Guangdong Province, 510000, People’s Republic of ChinaCorrespondence: Ruliu Li, Science and Technology Innovation Center,Guangzhou University of Chinese Medicine, No. 12, Jichang Road, Baiyun District, Guangzhou City, Guangdong Province, 510000, People’s Republic of China, Tel +86-020-39357088, Email lrl@gzucm.edu.cn Shaoju Guo, Gastroenterology Department, The Fourth Clinical Medical College, Guangzhou University of Chinese Medicine, No. 1, Fuhua Road, Shenzhen City, Guangdong Province, 518000, People’s Republic of China, Tel +86-0755-82571384, Email gsj1080@163.comPurpose: Kuiyangling is a traditional Chinese medicine formula used for the treatment of ulcerative colitis, but the specific mechanism remains unclear. Imbalance in NETs regulation is one of the important factors contributing to the onset of ulcerative colitis (UC). The HuR/VDR signaling pathway plays a significant role in restoring the intestinal mucosal barrier in UC. The aim of this study is to explore the mechanism of Kuiyangling in the treatment of ulcerative colitis.Methods: A mouse model of ulcerative colitis using 3% DSS water was considered, and model, normal, Kuiyangling medium- (5 g·kg− 1) and high-dose (10 g·kg− 1), and mesalazine (50 mg·kg− 1) groups were created. Measurements of colon length, spleen index, histopathological variances, subcellular structure observations, ROS content, and NET-related proteins (PAD4, MPO, citH3) were obtained through HE staining, electron microscopy, live imaging, and Western blotting assays. Immunohistochemistry and immunofluorescence analyses were conducted to assess the levels of HuR/VDR protein complex, ZO-1, Occludin, Claudin-7, and intestinal NETs. An ELISA kit was utilized to determine cytokine levels, LC-MS was performed to analyze the composition of Kuiyangling, and next-generation sequencing was conducted for detection of the intestinal mucosal transcriptome.Results: Kuiyangling reduced DAI, splenic index, and ROS content; maintained mucosal structure; decreased inflammation; and increased colon length and body mass index. Western blotting indicated that Kuiyangling reduced PAD4,MPO, and citH3 levels. Kuiyangling decreased NETs and increased the expression levels of ZO-1, Occludin, and Claudin-7, as well as up-regulating HuR, VDR, and HuR/VDR proteins. Kuiyangling reduced IL-1β, IL-6, and TNF-α levels while increasing TGF-β, IL-10, and IL-37 levels. Kuiyangling reduced inflammatory response proteins and elevated the levels of anti-inflammatory and intestinal barrier proteins, possibly inhibiting the TNF and oxidative phosphorylation signaling pathways.Conclusion: Kuiyangling enema in treating ulcerative colitis in mice, associated with a reduction in intestinal NETs and enhancement of HuR-mediated intestinal barrier signaling pathways. Keywords: ulcerative colitis, enema therapy, neutrophil extracellular traps, Chinese medicine, inflammation